The refining of titanium by crucibleless zone melting method - Kozhevnikov, O.E.; Pylypenko, M.M.; Shcherban, A.P.; Datsenko, О.А.; Pelykh, V.M.; Virych, V.D. (Вопросы атомной науки и техники, 2021)
The physical substantiation of titanium refining by crucibleless electron beam zone melting (ZM) method in vacuum was presented. Calculations of the equilibrium, limiting and effective distribution coefficients for impurity elements in the base metal were carried out. The refining of titanium was studied experimentally, and samples with a purity of 99.92 wt.% were received. The total content of impurities was reduced by a factor of 1.5 (from 0.12 to 0.08 wt.%). The concentration of interstitial impurities was significantly reduced (oxygen – by 1.3; carbon – by 2; nitrogen – by 2.5 times). The structure and microhardness were investigated. Представлено фізичне обґрунтування рафінування титану методом безтигельного електроннопроменевого зонного плавлення у вакуумі. Проведено розрахунки рівноважного, граничного та ефективного коефіцієнтів розподілу для домішкових елементів в основному металі. Експериментально досліджено рафінування титану, отримано зразки чистотою 99,92 мас.%. Сумарний вміст домішок знижено в 1,5 рази (з 0,12 до 0,08 мас.%). Значно зменшена концентрація домішок впровадження (кисню – в 1,3; вуглецю – в 2; азоту – в 2,5 рази). Досліджено структуру та мікротвердість. Представлено физическое обоснование рафинирования титана методом бестигельной электроннолучевой зонной плавки в вакууме. Проведены расчеты равновесного, предельного и эффективного коэффициентов распределения для примесных элементов в основном металле. Экспериментально исследовано рафинирование титана, получены образцы чистотой 99,92 мас.%. Суммарное содержание примесей снижено в 1,5 раза (с 0,12 до 0,08 мас.%). Значительно уменьшена концентрация примесей внедрения (кислорода – в 1,3; углерода – в 2; азота – в 2,5 раза). Исследована структура и микротвердость.